ROLE OF LOCAL AUTHORITY FOR IMPLEMENTING RTE: A CRITICAL ANALYSIS OF SECONDARY SCHOOLS AT THE BALI-I & BALI-II PANCHAYAT AREAS FROM GOSABA IN WEST BENGAL, INDIA - MANDAL, SUDIP (International Journal of Research -GRANTHAALAYAH, 2021)
Abstract: This study mainly in respect of the RTE Act. 2009 implementing phase and the actual accountabilities as local self government (Bali-I & Bali-II panchayat) to actualize the execution of RTE. It is indicate of intensive study on a particular case and it is not a critical approach but an exploratory study. This study had been done following the descriptive survey method. The present researcher has been collected primary, secondary data through the questionnaires, interview sheets, various reports and other relevant sources. Main purposes of present study is to focus the role of local self government as the monitoring agencies to execute RTE, so that common people as both urban and rural areas will be able to know actual what types as educational privileges they can consume from state authority. Major findings of this study are that headmasters have given positive feedback about the local government for cooperating and Local self government plays a particularly important role as the main partner of the Right to Education and it is preferred by most students and teachers.